The Relationship Between Religiosity and Preference for Leaders with Integrity: A Perspective on Religious Dimensions and Political Ethics - Mashluchah, Luluk; Ulum, Nuzulul; Halid, Ahmad; Machfudz (Millati: Journal of Islamic Studies and Humanities, 2025)
This study aims to analyze the relationship between religiosity and the preference for leaders with integrity, as well as examine the role of political ethics as a moderator in this relationship. Using a quantitative approach with a descriptive and correlational design, this research involved 185 respondents selected through purposive sampling. Data were collected using a Likert-scale-based questionnaire and analyzed using Moderated Regression Analysis (MRA). The findings indicate that religiosity has a positive relationship with the preference for leaders with integrity; however, this relationship is strengthened by an individual's level of political ethics. Individuals with high political ethics are more consistent in selecting leaders based on integrity, whereas those with low political ethics are more influenced by external factors such as political affiliation, social pressure, and economic conditions. Additionally, this study identifies that party loyalty, socioeconomic background, media influence, and social norms can either strengthen or weaken the relationship between religiosity and integrity-based leadership preferences. These findings reaffirm that religiosity is not the sole determining factor in voter decision-making; rather, it must be understood within the context of political ethics and other external influences. The implications of this research highlight the necessity of political education based on ethical values and integrity to cultivate more critical and rational voters in selecting leaders with integrity.